Analysis of match report indicators in men`s volleyball Olympics and world championships (2014-2021) depending on the type of final score - Giatsis, G.; Drikos, S.; Lola, A. (International Journal of Sports Science & Coaching, 2022)
The purpose of this study was to explore the match and technical indicators between winning and losing teams in the Olympics and World Championships (2016-2021) depending on the final score of the matches. A total of 273 volleyball match reports were analyzed from the Men`s Olympics (2016 and 2021) and World Championships (2014-2018). Discriminant function analysis determined which skill(s) contributed significantly to winning in matches with various score types. This study showed that for 3- and 4-set matches attack was the best predictor for team`s success, while block and serve had also meaningful contribution. In 5-set matches serve and block points were the main predictors of a team`s success. The results on the importance of scoring skills highlight the necessity of sustained trainability of all match actions, not favoring one, such as attack, too much. The essential for this balance is confirmed by the fact that teams do not increase their probability of winning a match by success only in attack, but also in the other terminal actions such as serve and block.